Tailored text‐messaging versus standard Quitline telephone counselling for smoking cessation among people who smoke from a low‐socio‐economic status background in Australia: A study protocol for a non‐inferiority randomized controlled trial (The Quit By Phone Study) - Howard, Bridget C.; Donnelly, Sorcha; McRobbie, Hayden; Barker, Daniel; Petrie, Dennis; Stockings, Emily; Brown, Jamie; Naughton, Felix; Whittaker, Robyn; Shakeshaft, Anthony; Patel, Kieran; Anderson, Jack; et al. (Addiction, 2025)
Background and aims: Signficant inequalities in tobacco smoking exist, with higher smoking rates among people from low‐socio‐economic status (low‐SES) populations. Tailored technology‐based programs for low‐SES smoking populations have the potential for high reach, but require effectiveness data from large‐scale trials. This trial among Australians who smoke from a low‐SES background will determine the effectiveness and cost‐effectiveness of tailored text‐message (TTM) support compared with standard Quitline (SQL) telephone support service. Design, setting and participants: This is a two‐arm, parallel group, randomized, non‐inferiority trial with allocation concealment and blinded outcome assessment in an Australian population within the greater Sydney region in New South Wales. Participants are adults who smoke daily (n = 1246), are interested in quitting and currently receiving a government pension or allowance, and will be recruited via advertisements. Intervention and comparator: Participants will be randomized (1:1 ratio) to receive either 12 months of TTM quit support or enrolment in SQL telephone support. Measurements: Assessments will be completed at baseline (telephone interview), within 1 month (check‐in call), at 3 months (on‐line questionnaire) and 12 months (telephone interview) post‐randomization. The primary outcome will be 6‐month continuous abstinence verified by carbon monoxide breath test at 12‐month follow‐up. The study will test whether TTM is non‐inferior to SQL by a non‐inferiority margin of 2%, i.e. the quit rate in the TTM group will be no worse than 2% less than the quit rate in the SQL group. Secondary outcomes will include self‐reported continuous and point prevalence abstinence and acceptability and cost‐effectiveness of TTM versus SQL. Conclusion: Should the tailored text‐message support prove non‐inferior and more cost‐effective than Quitline for this population, this will provide an opportunity for the upscaling of an effective, inexpensive and tailored quit support service. The trial findings will inform cessation treatment policy for priority populations in Australia and globally.